2015
DOI: 10.1142/s0219635215500077
|View full text |Cite
|
Sign up to set email alerts
|

Opposing motion inhibits responses of direction-selective ganglion cells in the fish retina

Abstract: Inhibitory influences in receptive fields (RFs) of the fish retinal direction-selective ganglion cells (DS GCs) were investigated. Responses of the fast retinal DS GCs were recorded extracellularly from their axon terminals in the superficial layer of tectum opticum of immobilized fish. The data were collected from two cyprinid species - Carassius gibelio, a wild form of the goldfish, and the barbel fish Labeobarbus intermedius. Visual stimuli were presented to the fish on the monitor screen within a square ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…3(b); the data processed in 164 cells]. The results of our recent experiments performed in carp, roach, and barbell¯sh Labeobarbus intermedius indicated that DS GCs of these¯shes coincided with retinal DS units of C. gibelio (Damjanović et al, 2015). Results conrming our¯ndings have been recently published by Nikolaou et al (2012).…”
Section: Classi¯cation Of Gold¯sh Ds Gcs By Preferred Directions and mentioning
confidence: 55%
See 3 more Smart Citations
“…3(b); the data processed in 164 cells]. The results of our recent experiments performed in carp, roach, and barbell¯sh Labeobarbus intermedius indicated that DS GCs of these¯shes coincided with retinal DS units of C. gibelio (Damjanović et al, 2015). Results conrming our¯ndings have been recently published by Nikolaou et al (2012).…”
Section: Classi¯cation Of Gold¯sh Ds Gcs By Preferred Directions and mentioning
confidence: 55%
“…This assumption can be supported by the fact that the gold¯sh DS units were shown to respond to a broad range of velocities of moving stimuli (from 2-30 /s) (Maximov et al, 2005b), similarly as shown for fast DS GCs of the mammalian retina (see review of Vaney et al, 2001). Direction selectivity in the¯sh DS GCs was shown to be produced by the null-side inhibition (Damjanović et al, 2015), and in this respect these units also resemble the fast DS GCs of mammals (Fried et al, 2002(Fried et al, , 2005Poznanski, 2005Poznanski, , 2010. However, it is important to note that our experiments as well as study of Nikolaou et al (2012) revealed some essential di®erences between¯sh and mammalian DS GCs.…”
Section: Summary and New Aspects Of Researchmentioning
confidence: 87%
See 2 more Smart Citations
“…The data progressively collected over a long period of time call into question the absolute meaningfulness of the "detector сoncept." So in fish, characterized by the enormous taxonomic, ecological and ethological diversity, one and the same set of retinal feature detectors was described in the TO of all of the studied species (Cronly-Dillon, 1964;Damjanovi c, Maximova, Aliper, Maximov, & Maximov, 2015;Jacobson & Gaze, 1964;Liege & Galand, 1971;Maximov et al, 2005aMaximov et al, , 1971Zenkin & Pigarev, 1969). Furthermore, practically the same set of specialized GCs was described in retinae of various mammals (Masland, 2012;O'Brien et al, 1999;van Wyk et al, 2006;Venkataramani & Taylor, 2010).…”
Section: Facts That Contradict the "Detector Concept"mentioning
confidence: 98%